Additions and corrections to the type list of Heteroptera (Insecta: Hemiptera) of the Costa Lima Collection, Oswaldo Cruz Foundation - Rodrigues, Juliana Mourão Dos Santos; Cordeiro, Isabelle Da Rocha Silva; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2017)
The Costa Lima collection, housed at the Oswaldo Cruz Foundation, has more than 6000 specimens and 5000 microscope slides. The type specimens of Heteroptera contained in this collection have been target of a few studies between 1944 and 2014, but thorough curatorial work has revealed inconsistencies in the lists that were published previously. We present herein additions and corrections to the lists of heteropteran types of the Costa Lima Collection, a summary table with the information gathered from the collection and the literature, and habitus images for 92 type specimens in six families.